Endovascular techniques in the treatment and prevention of cerebrovascular pathology - S. V. Tyaglyy (Zaporožskij Medicinskij Žurnal)
Aim. Cerebrovascular disease (CVD) is one of the most pressing health and social problems throughout the world and in particular in Ukraine. Specialized care for patients with cerebrovascular disease is fully possible on the basis of the regional hospital in the Zaporozhye region.